Two seasons' experience with pandemic A H1N1 influenza infection in neonates - Martic, Jelena; Savic, Natasa; Jankovic, Borisav; Nedeljkovic, Jasminka; Rakonjac, Zorika; Pejic, Katarina; Markovic-Sovtic, Gordana (The Turkish Journal of Pediatrics, 2012)
There are only a few reports on influenza A H1N1 infection in neonates. In this paper, we present our additional experience on the clinical characteristics, epidemiology and treatment of influenza A H1N1 (2009) infection in 10 newborn infants (aged 9-24 days). Influenza A H1N1 infection was confirmed by real-time reverse transcription-polymerase chain reaction of the nasopharyngeal swab specimens. The majority of neonates presented with fever, respiratory symptoms and lethargy. The respiratory illness ranged from mild symptoms to severe pneumonia requiring mechanical ventilation. Antiviral treatment with oseltamivir was started in five patients (50%). One lethal outcome was observed, while nine patients (90%) had complete recovery. To our knowledge, this is the largest presented series of neonatal cases with different clinical symptoms. We discuss the necessity of initiation of oseltamivir in infants with different clinical features.